2005
DOI: 10.1124/mol.105.013961
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Endocannabinoid Formation in Brain Slice Cultures through Activation of Group I Metabotropic Glutamate Receptors

Abstract: Activation of group I metabotropic glutamate (mGlu) receptors drives the endocannabinoid system to cause both shortand long-term changes of synaptic strength in the striatum, hippocampus, and other brain areas. Although there is strong electrophysiological evidence for a role of endocannabinoid release in mGlu receptor-dependent plasticity, the identity of the endocannabinoid transmitter mediating this phenomenon remains undefined. In this study, we show that activation of group I mGlu receptors triggers the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(179 citation statements)
references
References 44 publications
7
166
1
2
Order By: Relevance
“…In support of this, it has been shown that mGluR5 colocalizes with diacylglycerol lipase-␣, the synthetic enzyme of the endocannabinoid 2-arachidonoylglycerol (2-AG), in perisynaptic regions of striatal medium spiny neurons (Uchigashima et al, 2007). In addition, group I mGluR activation initiates 2-AG biosynthesis (Jung et al, 2005) and endocannabinoid-mediated synaptic plasticity in several other brain regions (Ohno-Shosaku et al, 2002;Zhu and Lovinger, 2005;Grueter et al, 2006;Centonze et al, 2007;Uchigashima et al, 2007). In the present study, we have not identified the endocannabinoid involved; however, anandamide and 2-AG are potential candidates, because they are both produced within the PAG under certain conditions (Walker et al, 1999;Hohmann et al, 2005).…”
Section: Glutamate Spillover Drives Endocannabinoid Signalingmentioning
confidence: 98%
“…In support of this, it has been shown that mGluR5 colocalizes with diacylglycerol lipase-␣, the synthetic enzyme of the endocannabinoid 2-arachidonoylglycerol (2-AG), in perisynaptic regions of striatal medium spiny neurons (Uchigashima et al, 2007). In addition, group I mGluR activation initiates 2-AG biosynthesis (Jung et al, 2005) and endocannabinoid-mediated synaptic plasticity in several other brain regions (Ohno-Shosaku et al, 2002;Zhu and Lovinger, 2005;Grueter et al, 2006;Centonze et al, 2007;Uchigashima et al, 2007). In the present study, we have not identified the endocannabinoid involved; however, anandamide and 2-AG are potential candidates, because they are both produced within the PAG under certain conditions (Walker et al, 1999;Hohmann et al, 2005).…”
Section: Glutamate Spillover Drives Endocannabinoid Signalingmentioning
confidence: 98%
“…Slices were pre-incubated with the mGlu5 receptor antagonist MPEP (Gasparini et al, 1999) at 5 µM (Jung et al, 2005). Slices were exposed to MPEP for 10 minutes after which DHPG was applied ( Figure 2E).…”
Section: Dhpg-induced Bursting In Area Ca1 Is Activity-dependent and mentioning
confidence: 99%
“…In particular, the endocannabinoid 2-AG has been directly implicated in mGlur-induced retrograde signalling in the hippocampus, cerebellum and other regions of the brain [60][61][62] . It is envisaged that 2-AG may be produced in dendritic spines, through activation of type I mGlurs and the transducing G-protein G q/11 , which are coupled to the phospholipase C/DAG lipase (DGl) pathway (fIG.…”
Section: Flippasementioning
confidence: 99%
“…4). Glutamate (blue circles) released from excitatory axon terminals activates postsynaptic type I metabotropic glutamate receptors (mGluR), stimulating 2-AG production through the phospholipase C-β (PLC-β)/diacylglycerol lipase (DGL) pathway 60 (fIG. 4).…”
Section: Flippasementioning
confidence: 99%